ANALISA PENGARUH KATALIS TEMBAGA PADA KATALYTIK KONVERTER TERHADAP EMISI GAS CARBON MONOKSIDA DAN HIDRO KARBON PADA KENDARAAN MOTOR BENSIN - Mustaqim .; Tofik Hidayat; M. Ginta Nur Hidayat (Engineering : Jurnal Bidang Teknik, 2011)
The growth of motor vehicles in Indonesia is quite fast to bring the influence of the increased usage of fuel oil, so that the air pollution becomes inevitable. Motor vehicles are the largest source of pollutant emissions and contribute to the Carbon Monoxide of the pollutants that exist, where from year to year pollution levels increased along with the increasing use of motor vehicles. One of the things that can be done by researchers in this application is the installation of emission control teknology Catalytic Converters are installed in the exhaust gas channel.  Catalytic Converter generally use this type of expensive metal catalysts and rare in the market (Palladium, Platinum and Rhodium). Based on the fact above, so we do by making "'Design of CatalyticConverter with using metal copper (Cu) as catalyst.This research aims to design a catalytic converter get up, to know the efficiency of the use of metals Copper (Cu) as a catalyst and to determine the effect of CO emissions in motor vehicles.  Measurement  of the concentration of Carbon Monoxide gas emissions in the exhaust gas channel carried on standart conditions using Gas Analyzer tool. From the results of this in I find that the use of Catalytic Converters Copper (Cu) with a variety plate and the fibers  are made of copper as a catalyst to reduce CO Flue gas emissions. Efficiency decrease in CO concentration of 0.01% by using 0.2 mm Cu and copper fibers. Output CO concentration are largely influenced by changes in engine speed and vehicle fuel and air mixture entering the combustion chamber. In general, the use of Catalytic Converter does not affect the performance of vehicle engines. Keywords:    Catalytic Converters, Catalytic Copper (Cu), Concentrations of CO